EFFECTS OF LEADERSHIP, RISK-TAKING, INNOVATION, INTENSIVE PARTICIPATION AND CONTRIBUTION PARTICIPATION ON THE PERFORMANCE OF COOPERATIVE IN BANYUMAS, CENTRAL JAVA - Akhmad Darmawan; Suyoto Suyoto; Hengky Widhiandono; Ahmad Zainal Abidin bin Abd Razak; Hariyaty Binti Ab Wahab (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to analyze effects of leadership, risk-taking, innovation, intensive participation and contribution participation on the performance of cooperative in banyumas, central java. The method used is multiple regression analysis using the analytical methods F-test, R2 test, and t-test. Based on the results of the tests and discussions that risk-taking, innovation, and intensive participation are impacting the performance of co-operative managers in Banyumas, Central Java, Indonesia. Leadership and participation have not effect the performance of co-operative managers in Banyumas, Central Java, Indonesia. Keywords: Leadership, Risk Taking, Innovation, Intensive Participation, Contributive Participation.